Redevelopment and reuse of nuclear facilities and sites : case histories and lessons learned - Laraia, M. (IAEA nuclear energy series, 2011)
"Evaluating potential reuse/redevelopment options for nuclear facilities is an important aspect of the decommissioning process. Early planning for site reuse can facilitate the transition from operation to decommissioning and subsequently to new, profitable uses of the site. At the same time, it can reduce the financial burden associated with decommissioning and alleviate the overall impact on the local community. This publication provides an overview of completed decommissioning projects worldwide and successful ways to reuse decommissioned sites for new purposes, whereby extensive use is made of non-nuclear experience. Lessons learned from these projects and practical guidance are highlighted"--Provided by publisher.